Managing millennials for dummies - Ubl, Hannah L.; Walden, Lisa X.; Arbit, Debra (--For dummies., 2017)
Packed with insight, advice, personal anecdotes, and practical guidance, this book shows you how to manage your Millennial workers and teach them how to manage themselves. --